Association of Pre Hospital Steroid and Antibiotic Use with Hematological Severity and Liver Injury in Dengue Patients in Karachi Outbreak: A Cross Sectional Study - Kiran Khan, Nadia Zohair, Alfarah Rehmatullah, Ghazal Irfan, Sidra Khalid, Muhammad Aitmaud Uddolah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inappropriate pre-hospital steroid and antibiotic use is common in dengue outbreaks in Karachi but little is known about how these treatments affect liver damage and hematological severity. The purpose of this study was to evaluate the relationship between pre-hospital exposure to steroids and antibiotics and laboratory-based severity markers in dengue patients during a recent outbreak. Methodology: Over the course of four months a cross-sectional questionnaire-based study involving 130 dengue-positive patients was carried out at a tertiary care hospital in Karachi. Demographics pre-hospital steroid and antibiotic use and clinical course were recorded using a structured questionnaire given by the interviewer. Chi-square tests t-tests and multivariable regression were used to adjust for age sex comorbidities and dengue severity. Hematological severity (platelet count hemoconcentration) and liver injury markers (ALT AST bilirubin albumin) were taken from hospital records. Results: Antibiotic use was reported in 44. 6% of patients and steroid use in 31.5% of patients prior to hospitalization. The median platelet count was lower in steroid-exposed patients (42.0 vs. 68.5 × 10⁹/L; p < 0.001) higher rates of severe thrombocytopenia (68.3% vs. 23.6%; p < 0.001) and more hemoconcentration (53.7% vs. 26.9%; p = 0.004). They also showed higher ALT ((124.0 vs. 82.0 U/L; p < 0.001) and AST with 34. 1 percent exhibiting severe transaminitis (ALT >5× ULN) as opposed to 5.6% for non-users. Pre-hospital steroid use was verified by multivariable analysis as an independent predictor of elevated transaminases and severe thrombocytopenia (p < 0.001). Use of antibiotics by itself did not exhibit any meaningful independent correlations. Patients exposed to steroids experienced longer hospital stays more ICU admissions and a non-significant trend toward increased mortality. Conclusion. In Karachi dengue patients’ pre-hospital steroid use is significantly linked to increased hematological severity and liver damage while antibiotics by themselves did not demonstrate similar independent effects. During dengue outbreaks routine community-level steroid prescriptions should be discouraged. To improve guideline-adherent management specific educational interventions for primary care and pharmacy-level providers are required. Keywords: Pre‑Hospital Steroid, Antibiotic, Hematological Severity, Liver Injury, Dengue, Karachi